Gender equity: educating to respect differences beyond false myths and stereotypes - Gina Chianese (Firenze University Press, 2024)
Gender equality is the basis of fundamental human rights as emphasised in several national and international documents. However, the data send us a picture of inequalities that are rooted in women's biographies already in childhood and that, through stereotypes and expectations, condition behaviour and desires, access to studies and career paths. In this scenario, education represents a fundamental key to allow the development of renewed awareness from which to undo gender (Biemmi & Lionelli, 2016) in favour of an education to differences and the plurality of differences (Padoan & Sangiuliano, 2008).   Equità di genere: per educare al rispetto delle differenze oltre i falsi miti e gli stereotipi. L'uguaglianza di genere è alla base dei diritti fondamentali della persona così come sottolineato in diversi documenti a carattere nazionale e internazionale. Tuttavia, i dati ci rimandano una fotografia fatta di diseguaglianze che si radicano nelle biografie delle donne già nell'infanzia e che, attraverso stereotipi e aspettative, condizionano comportamenti e desideri, l'accesso agli studi e percorsi di carriera. In questo scenario l'educazione rappresenta una chiave di volta fondamentale per consentire lo sviluppo di rinnovate consapevolezze a partire dalle quali disfare il genere (Biemmi & Lionelli, 2016) a favore di un'educazione alle differenze e alla pluralità delle differenze (Padoan & Sangiuliano, 2008).